Assessment of health literacy level in participants of the "Woman — Health Model" project in the Yamalo-Nenets Autonomous Okrug - E. V. Usova; M. V. Lopatina; A. V. Kontsevaya; S. A. Tokarev; N. S. Polovodova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Public health enhancement system in Russia includes a number of main components, one of which is measures aimed at increasing the population’s health literacy, creating a healthy lifestyle civility and a responsible attitude to health. An important social group of influence are women. Women's health literacy enables them to participate in health promotion activities and engage their communities in healthy lifestyles at local public level.Aim. To study the health literacy level among "Woman — Health Model" project participants in the Yamalo-Nenets Autonomous Okrug.Material and methods. An online survey of "Woman — Health Model" project participants aged ≥18 years was conducted using a validated and adapted HLS19-RUS questionnaire, developed on the basis of international questionnaire of World Health Organization Network on Measuring Population and Organizational Health Literacy (M-POHL). Health literacy (HL) was studied by means of standardized indices for four HL levels as follows: low, problematic, sufficient, excellent. Frequency analysis and associations of HL with socio-demographic characteristics of Yamal women. Also, navigational HL of women was studied for the first time. Statistical data processing was carried out using SPSS 23.0 for Windows and MS Excel 2016 software.Results. Of the 2000 women participating in the Project, 1445 took part in the survey. The response rate was 72,25%. The results showed that 27,0% of participants had insufficient HL in disease prevention, assessment and use of health information. The most vulnerable groups were identified, which include women aged ≥65 years without higher education and job. Women participants in the Project from the YamaloNenets Autonomous Okrug encounter the greatest difficulties with regard to navigational HL (53,3%) — the ability to navigate services, changes, innovations and specialists of the healthcare system.Conclusion. The results obtained made it possible to further adapt the training program for Project participants taking into account the identified level of HL and the difficulties women face in regard to health information.